Age and size at maturity: A quantitative review of diet‐induced reaction norms in insects. (24th September 2014) - Teder, Tiit; Vellau, Helen; Tammaru, Toomas
Abstract : Optimality models predict that diet‐induced bivariate reaction norms for age and size at maturity can have diverse shapes, with the slope varying from negative to positive. To evaluate these predictions, we perform a quantitative review of relevant data, using a literature‐derived database of body sizes and development times for over 200 insect species. We show that bivariate reaction norms with a negative slope prevail in nearly all taxonomic and ecological categories of insects as well as in some other ectotherm taxa with comparable life histories (arachnids and amphibians). In insects, positive slopes are largely limited to species, which feed on discrete resource items, parasitoids in particular. By contrast, with virtually no meaningful exceptions, herbivorous and predatory insects display reaction norms with a negative slope. This is consistent with the idea that predictable resource depletion, a scenario selecting for positively sloped reaction norms, is not frequent for these insects. Another source of such selection—a positive correlation between resource levels and juvenile mortality rates—should similarly be rare among insects. Positive slopes can also be predicted by models which integrate life‐history evolution and population dynamics. As bottom‐up regulation is not common in most insect groups, such models may not be most appropriate for insects.